PENTINGNYA MEMAHAMI HADIS DENGAN MEMPERTIMBANGKAN SETTING HISTORIS PERSPEKTIF YŪSUF AL-QARAḌAWĪ - Suryadi Suryadi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Yusuf al-Qaradhawi is one of scholars who considered historical seting as acompulsory in understanding Hadith. He set into three categories of classification: Understanding Hadith based on the cause and its specific background; understanding Hadith by considering the purposefulness and judiciousness of the Prophet, as well understanding hadith by taking temporal customs of the Prophet era into account. Thus historicity as an approach in Hadith studies is a useful insight in the study chronological condition when hadith were transmitted and disseminated. Numbers of questions such as why Prophet had said such hadith, to what extent of socio-cultural condition and situation as well as it’s political circumstance had the Prophet declared and stated that Hadith, as well as exploration on what type of factors which entailed such kind of matan Hadith had existed; those are parts of analytical aspects of a historical approach in Hadith Studies.